THE EFFECT OF AUDIT COMMITTEE CHARACTERISTICS, HUMAN CAPITAL PERFORMANCE, AND AUDIT QUALITY ON HUMAN CAPITAL DISCLOSURE - Florensi, Elvina; Laturette, Kazia (International Journal of Application on Economics and Business, 2025)
This study seeks to analyze the influence of audit committee characteristics, human capital performance, and audit quality on human capital disclosure and audit committee size in the financial services sector during the COVID-19 pandemic from 2020 to 2021. This article analyzes Human Capital Disclosure via the lens of auditing. This study utilizes multiple linear regression methods with STATA software version 16. This study suggests that the financial acumen of audit committees and the quality of audits significantly affect human capital disclosure. The human capital performance variable negatively affects human capital performance. However, the dimensions of audit committee size and meeting frequency do not affect human capital performance. The study's findings reveal that investors evaluate a company's standing beyond simple financial measurements, including profit and loss.